2006
DOI: 10.1242/dev.02585
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger genesFezandFez-likefunction in the establishment of diencephalon subdivisions

Abstract: Fez and Fez-like (Fezl) are zinc-finger genes that encode transcriptional repressors expressed in overlapping domains of the forebrain. By generating Fez;Fezl-deficient mice we found that a redundant function of Fez and Fezl is required for the formation of diencephalon subdivisions. The caudal forebrain can be divided into three transverse subdivisions: prethalamus (also called ventral thalamus), thalamus (dorsal thalamus) and pretectum. Fez;Fezl-deficient mice showed a complete loss of prethalamus and a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 69 publications
6
132
0
Order By: Relevance
“…mice; AK014242 and AB042399) (Hirata et al, 2006b). Because of the presence of EH1, Fez is thought to function as a transcriptional repressor (Hirata et al, 2006a). After confirming the microarray result that, during blastula stages, H. pulcherrimus FoxQ2 morphants have significantly decreased fez mRNA levels by in situ hybridization and QPCR ( Fig.…”
Section: Fez Expression Depends Strongly On Foxq2 During Blastula Stagesmentioning
confidence: 53%
See 2 more Smart Citations
“…mice; AK014242 and AB042399) (Hirata et al, 2006b). Because of the presence of EH1, Fez is thought to function as a transcriptional repressor (Hirata et al, 2006a). After confirming the microarray result that, during blastula stages, H. pulcherrimus FoxQ2 morphants have significantly decreased fez mRNA levels by in situ hybridization and QPCR ( Fig.…”
Section: Fez Expression Depends Strongly On Foxq2 During Blastula Stagesmentioning
confidence: 53%
“…Downregulation of BMP signaling along the aboral side of the animal plate by Fez function is probably cell autonomous, although the possibility that Fez induces a short-range signal cannot be strictly ruled out. So far, because the sequence of Fez suggests that it acts as a transcriptional repressor (Hirata et al, 2006a) rather than a Smad-interacting protein, such as SIP1 (Verschueren et al, 1999;van Grunsven et al, 2003;van Grunsven et al, 2007), it is unlikely that Fez interferes directly with pSmad1/5/8 activity in intracellular regions. Thus, it is possible that Fez regulates a gene(s) that is involved in pathways to maintain pSmad1/5/8 levels, such as degradation, dephosphorylation, and/or nucleocytoplasmic shuttling of Smad (Inman et al, 2002;Chen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our manuscript was under review, it was reported that the mouse Fez and Fezl proteins together also play a crucial role in the establishment of the diencephalon divisions (Hirata et al, 2006a), suggesting an evolutionarily conserved role of the Fez-and Fezlgene families. Interestingly, a notable difference exists between zebrafish and mice: whereas our LOF and GOF analyses indicate a clear role of zebrafish fezl in promoting the prethalamus and in repressing the ZLI, fez -fezl -double-mutant mouse embryos had a loss of both prethalamus and ZLI, but an expansion of caudal diencephalon (the thalamus and pretectum).…”
Section: Research Articlementioning
confidence: 99%
“…In the diencephalic neuroepithelium, Shh shows an intriguing and dynamic pattern of expression with domains in the caudal-dorsal diencephalon [zona limitans interthalamica (ZLI)] and the rostral-ventral diencephalon (hypothalamic domain), which seem strategically situated to influence the formation of the DTJ. In the caudal diencephalon, neural Shh from the ZLI specifies the prethalamus (PTh) (Hashimoto-Torii et al, 2003;Kiecker and Lumsden, 2004;Vieira et al, 2005;Hirata et al, 2006;Scholpp et al, 2006;Guinazu et al, 2007) and promotes growth and differentiation of specific subdivisions of the thalamus (Szabó et al, 2009). The role of neural Shh in the rostral diencephalon (hypothalamus) and DTJ, however, is only starting to be analyzed.…”
Section: Introductionmentioning
confidence: 99%